Linking Perceived Organizational Support and Self-Efficacy to Employee Performance in Public Service Organizations: The Mediating Role of Employee Engagement - Adhiyani, Muhammad Rayyan; Said, Laila Refiana; Claudia, Meiske; Anisah, Hastin Umi; Darullah, Muhammad Daral (Science Tech Group, 2025)
Employee performance is a critical factor determining the success of public service organizations. This study aims to examine the influence of perceived organizational support (POS) and self-efficacy on employee performance, with employee engagement serving as a mediating variable, among employees of PT Air Minum Bandarmasih (Perseroda). Using a quantitative approach, data were collected through questionnaires distributed to 252 employees, with 163 valid responses analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method in SmartPLS 3.0. The results show that POS has a significant positive effect on both employee engagement and performance, while self-efficacy significantly affects engagement but not performance directly. Employee engagement positively influences performance and mediates the effects of both POS and self-efficacy. Overall, the findings underscore the critical role of perceived organizational support, self-efficacy, and employee engagement in improving performance within public service organizations.